An APETALA3 homolog controls both petal identity and floral meristem patterning in Nigella damascena L. (Ranunculaceae). (14th August 2013) - Gonçalves, Beatriz; Nougué, Odrade; Jabbour, Florian; Ridel, Céline; Morin, Halima; Laufs, Patrick; Manicacci, Domenica; Damerval, Catherine
Summary Flower architecture mutants provide a unique opportunity to address the genetic origin of flower diversity. Here we study a naturally occurring floral dimorphism in Nigella damascena (Ranunculaceae), involving replacement of the petals by numerous sepal‐like and chimeric sepal/stamen organs. We performed a comparative study of floral morphology and floral development, and characterized the expression of APETALA3 and PISTILLATA homologs in both morphs. Segregation analyses and gene silencing were used to determine the involvement of an APETALA3 paralog (NdAP3–3) in the floral dimorphism. We demonstrate that the complex floral dimorphism is controlled by a single locus, which perfectly co‐segregates with the NdAP3–3 gene. This gene is not expressed in the apetalous morph and exhibits a particular expression dynamic during early floral development in the petalous morph. NdAP3–3 silencing in petalous plants perfectly phenocopies the apetalous morph. Our results show that NdAP3–3 is fully responsible for the complex N. damascena floral dimorphism, suggesting that it plays a role not only in petal identity but also in meristem patterning, possibly through regulation of perianth organ number and the perianth/stamen boundary.